Work Load Evaluation for Determining Human Resources Needs (Study of Emergency Room and General Clinic “Dokterku Taman Gading Clinic” Jember) - Edy Kurniawan; Al Munawir; Zarah Puspitaningtyas (Alliance oh Health Activists (AloHA), 2020)
The role of humans as a resource in an organization is increasingly believed to be of importance. Human resource planning is deemed necessary in order to improve employee efficiency, effectiveness and productivity. An evaluation of workload is deemed necessary in order to determine effective and efficient work productivity without ignoring the physical and psychological conditions of employees. Workload evaluation is also needed to determine the needs of Human Resources for relevant agencies. Clinic “Dokterku Taman Gading” experiences an increase in visit of patiens from year to year. This can affect employee work productivity so research is needed to evaluate employee workload with the Work Sampling method. This research method used direct observation of work activities on employees. This type of research was used analytic observational research. From a total sample of 4.800 observations, it knew that the productive activity of employees was 3825 (79.7%). The total standard time of each employee of “Dokterku Taman Gading”Clinic ± 1 minute per activity. The standard time per activity will be accumulated to determine the minimum standard service time given to each patient. Keywords: workload evaluation; HR planning; work sampling